SELF-EMPLOYMENT OF THE POPULATION: ANALYSIS AND RESULTS (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article presents the practical results achieved in the course of implementing measures and regulations adopted for self-employment of the unemployed population during the crisis caused by the COVID-19 pandemic that began in March 2020, and the level of risk for the economy on a global scale.
Keywords: self-employment, global wave, social guarantees, individual entrepreneurship, basic calculation amount, payment of social tax, "first step into business", "business in the neighborhood".